2016
DOI: 10.3390/f7090187
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Mortality within Natural Wildfire Events in the Western Canadian Boreal Forest: What Burns and Why?

Abstract: Abstract:Wildfires are a common disturbance event in the Canadian boreal forest. Within event boundaries, the level of vegetation mortality varies greatly. Understanding where surviving vegetation occurs within fire events and how this relates to pre-fire vegetation, topography, and fire weather can inform forest management decisions. We used pre-fire forest inventory data, digital elevation maps, and records of fire weather for 37 naturally-occurring wildfires (1961 to 1982; 30 to 5500 ha) covering a wide ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
1
12
1
Order By: Relevance
“…); however, this proportion was smaller than the 64% observed by Ferster et al. () in the same boreal plains ecoregion. Although area burned severely increases with increasing fire size, it has also been suggested that larger fires tend to have larger residual stands and a higher proportion of unchanged patches in the boreal forest (Eberhart and Woodard , Madoui et al.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…); however, this proportion was smaller than the 64% observed by Ferster et al. () in the same boreal plains ecoregion. Although area burned severely increases with increasing fire size, it has also been suggested that larger fires tend to have larger residual stands and a higher proportion of unchanged patches in the boreal forest (Eberhart and Woodard , Madoui et al.…”
Section: Discussioncontrasting
confidence: 61%
“…The fires studied here are of a substantial size, with only six fires burning more than 1,400,000 ha in a single year, an area equivalent to that burned by 295 fires over 26 yr in the montane study area examined by Harvey et al (2016b), and over four times the area burned by 125 fires over 24 yr in a study of the northern Cascade Range (Cansler and McKenzie 2014). The proportion experiencing complete mortality was much higher than the average proportions of stand-replacing fire observed in the western United States (Cansler and McKenzie 2014, Harvey et al 2016b; however, this proportion was smaller than the 64% observed by Ferster et al (2016) in the same boreal plains ecoregion. Although area burned severely increases with increasing fire size, it has also been suggested that larger fires tend to have larger residual stands and a higher proportion of unchanged patches in the boreal forest (Eberhart andWoodard 1987, Madoui et al 2010).…”
Section: Landscape Patterns Of Burn Severity In the Northwestern Borementioning
confidence: 87%
See 2 more Smart Citations
“…While this approach is unique to Australia, such patterns of recovery are not (e.g., [99,100]). Furthermore, with variation in post fire conditions [27] or fire severity [101,102] having the potential to influence vegetation recovery, using time since fire as the sole moderator of fuel properties may not necessarily deliver outcomes that meet manager's expectations. Additionally, fire is only one of many potential disturbances that can impact fuels-it may also be important to recognise other disturbances such as timber harvesting or drought.…”
Section: Summarizing Fuel To Develop Mapsmentioning
confidence: 99%